Avaliação da atividade antioxidante e antiproliferativa do extrato aquoso de frutas tropicais - Barros, Joanna de ângelis da Costa (2012)
The antioxidant activity of aqueous extracts of five edible tropical fruits (Spondias lutea, Hancornia speciosa, Spondias purpurea, Manilkara zapota and Averrhoa carambola) was investigated using different methods. The amount of phenolic compounds was determined by the Folin-Ciocalteu reagent. The M. zapota had Total Antioxidant Capacity (TAC) higher than the other fruits. Extracts showed neither reducing power nor iron chelation (between 0.01 and 2.0 mg/mL). H. speciosa exhibited the highest superoxide scavenging activity (80%, 0.5 mg/mL). However, at high concentrations (8.0 mg/mL) only A. carambola, S. purpurea and S. lutea scavenging 100% of radicals formed. M. zapota and S. purpurea had higher phenolic compound levels and greater OH radical scavenging activity (92 %, 2.0 mg/mL). Antiproliferative activity was assessed with 3T3 fibroblasts and cervical tumor cells (HeLa). The most potent extract was S. purpurea (0.5 mg/mL), which inhibited HeLa cell proliferation by 52%. The most fruits showed antioxidant and antiproliferative properties, characterizing them as functional foods.